Guatemala : Report on Observance of Standards and Codes; Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2006)
This report provides an assessment of fiscal transparency practices in Guatemala in light of the requirements of the IMF Code of Good Practices on Fiscal Transparency. The assessment reveals that Guatemala has progressed in certain important aspects of fiscal transparency. A variety of measures have made it possible to modernize budget, treasury, and accounting procedures, improve management and control of public funds, and prepare timely budget execution reports. The annual budget and the ministry of finance website provide increasingly complete information on central government activities.